Vitamin D. - Feldman, David, 1939-; Pike, J. Wesley; Bouillon, R. (Academic Press is an imprint of Elsevier, 2018)
"Vitamin D: Volume One: Biochemistry, Physiology and Diagnostics, Fourth Edition, presents the latest information from international experts in endocrinology, bone biology and human physiology, taking readers through the basic research of vitamin D. This impressive reference presents a comprehensive review of the multifaceted vitamin D. Researchers from all areas will gain insight into how clinical observations and practices can feed back into the research cycle, thus allowing them to develop more targeted genomic and proteomic insights on the mechanisms of disease. Offers a comprehensive reference, ranging from basic bone biology, to biochemistry, to the clinical diagnostic and management implications of vitamin DSaves researchers and clinicians time in quickly accessing the very latest details on the diverse scientific and clinical aspects of Vitamin D, as opposed to searching through thousands of journal articlesTargets chemistry, metabolism and circulation, mechanisms of action, mineral and bone homeostasis, human physiology, diagnosis and management, nutrition, sunlight, genetics and vitamin D deficiency. Volume II of this collection presents a clinical focus on disorders, analogs, cancer; immunity, inflammation and disease and therapeutic applications"--Publisher's description